Intergenerational persistence in health in developing countries: The penalty of gender inequality? - Sonia R. Bhalotra; Samantha Rawlings (Institute for the Study of Labor (IZA), 2010)
This paper is motivated to investigate the often neglected payoff to investments in the health of girls and women in terms of next generation outcomes. This paper investigates the intergenerational persistence of health across time and region as well as across the distribution of maternal health. It uses comparable micro-data on as many as 2.24 million children born of about 0.6 million mothers in 38 developing countries in the 31 year period, 1970-2000. Mother's health is indicated by her height, BMI and anemia status. Child health is indicated by mortality risk and anthropometric failure. We find a positive relationship between maternal and child health across indicators and highlight non-linearities in these relationships. The results suggest that both contemporary and childhood health of the mother matter and that the benefits to the next generation are likely to be persistent. Averaging across the sample, persistence shows a considerable decline over time. Disaggregation shows that the decline is only significant in Latin America. Persistence has remained largely constant in Asia and has risen in Africa. The paper provides the first cross-country estimates of the intergenerational persistence in health and the first estimates of trends.
Keywords: I10; J11; O57; 330; intergenerational persistence; mobility; health; developing countries; cohort trends; inequality; Gesundheit; Generationenbeziehungen; Geschlecht; Entwicklungsländer